Fecal microbiota transplantation ameliorates stress-induced depression-like behaviors associated with the inhibition of glial and NLRP3 inflammasome in rat brain. (May 2021) - Rao, Jingjing; Qiao, Yi; Xie, Ruining; Lin, Li; Jiang, Jian; Wang, Chunmei; Li, Gongying
Abstract: Background: Evidence from previous studies has demonstrated that the gut-microbiota-brain axis is vital in regulating of behavior and neuroinflammation in the central nervous system. Considering the putative connection among gut microbiota, neural function, and behavior, the present study investigated the potential signaling of gut microbiota to modulate depression-like behaviors and neuroinflammation. Methods: Rats showing depression-like behaviors induced by chronic unpredictable mild stress received fecal microbiota treatment or vehicle for 14 days, and alterations in behavior and neuroinflammation were assessed. ELISA, immunofluorescence staining and Western blot were used to analysis the activation of glial cells and NLRP3 inflammasome. Results: Treatment with fecal microbiota transplantation ameliorated depression-like behaviors. 5-Hydroxytryptamine decreased in the chronic unpredictable mild stress rat model but significantly increased after fecal microbiota transplantation. The treatment with fecal microbiota transplantation decreased the production of IL-1β and TNF-α. Moreover, fecal microbiota transplantation administration suppressed the activation of Iba1 positive microglia cells and GFAP positive astrocytes cells and reduced the expression of NLRP3, ASC, Caspase-1, and IL-1β pathway in the prefrontal cortex and hippocampus. Conclusions: Fecal microbiota transplantation can improve depression-like behaviors induced by chronic unpredictable mild stress. The anti-depression effects of fecal microbiota transplantation were associated with the suppressed activation of glial cells and NLRP3 inflammasome in the brain.